2021
DOI: 10.3390/su13105685
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Emission Reduction and Meteorological Change in PM2.5 and Transport Flux in Typical Cities Cluster during 2013–2017

Abstract: Under the Air Pollution Prevention and Control Action Plan (APPCAP) implemented, China has witnessed an air quality change during the past five years, yet the main influence factors remain relatively unexplored. Taking the Beijing-Tianjin-Hebei (BTH) and Yangtze River Delta (YRD) regions as typical cluster cities, the Weather Research Forecasting (WRF) and Comprehensive Air Quality Model with Extension (CAMx) were introduced to demonstrate the meteorological and emission contribution and PM2.5 flux distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…6). The percentages of PM MET 2:5 to PM OBS 2:5 from TSM, however, suggested the meteorology variations contributed to the reduction of the observed PM 2.5 in the YRD region, similar with previous studies with CTM adopted in YRD 49,50 . The opposite role of meteorology to the variation of PM 2.5 derived from different methods here and previous studies suggested that none of the existing methods can perfectly decouple the effects of emissions and meteorology on the trends of air pollutant concentrations.…”
Section: Contributions Of Emission and Meteorology To Pm 25 Trend By ...supporting
confidence: 89%
“…6). The percentages of PM MET 2:5 to PM OBS 2:5 from TSM, however, suggested the meteorology variations contributed to the reduction of the observed PM 2.5 in the YRD region, similar with previous studies with CTM adopted in YRD 49,50 . The opposite role of meteorology to the variation of PM 2.5 derived from different methods here and previous studies suggested that none of the existing methods can perfectly decouple the effects of emissions and meteorology on the trends of air pollutant concentrations.…”
Section: Contributions Of Emission and Meteorology To Pm 25 Trend By ...supporting
confidence: 89%
“…The initial meteorological and boundary conditions for the WRF were obtained from the National Centers for Environmental Prediction (NCEP) final operational model global analysis data with a 6 h temporal resolution and 1 • × 1 • spatial resolution (https://rda. ucar.edu/datasets/ds083.2/#!access, accessed on 20 May 2021), which is reliable and has been widely used in previous studies [16][17][18]. Global topography and land use data were provided by the United States Geological Survey (USGS).…”
Section: Model Configurationmentioning
confidence: 99%
“…Air contamination can be one of the most severe worldwide issues causing ecological and environmental damage [1][2][3] as well as damage to human fitness [4][5][6], especially under long-term high-PM 2.5 (diameter less than or equal 2.5 µg/m 3 ) concentration conditions, which would pose serious threats to public health and respiratory filtration systems. PM 2.5 is known as "pulmonary particulate matter" and is a key index for assessing fitness harm [7,8]. Therefore, an accurate understanding of PM 2.5 concentration is of great significance for early warning of atmospheric quality, which helps to reduce health damage and economic loss.…”
Section: Introductionmentioning
confidence: 99%